VD_FINDINFO Arrêt / 2015 / 28 vom 16. Dezember 2014 - VD Tribunal cantonal (2014)
MESURE PROVISIONNELLE, RELATIONS PERSONNELLES, COMPLÉMENT, ENQUÊTEEN GÉNÉRAL, DÉCISION DE RENVOI | 273 CC, 445 al. 1 CC